Designing Ethnomathematics-Enriched Teaching Materials for Fostering Mathematical Creative Thinking for Applications in Online Learning Environments - Rahmat Andri Kurniawan; Suherman Suherman; Komarudin Komarudin; Matteo Zarpellon; Ibrahim Khalil (Online Learning In Educational Research (OLER), 2023)
Integrating ethnomathematics into mathematics education holds tremendous promise, fostering a range of positive outcomes. It has shown potential in enhancing students' mathematical creative thinking, problem-solving abilities, active engagement in learning, and fostering a deeper appreciation for cultural diversity. Despite these promising prospects, an evident gap looms large in the literature specifically, the lack of comprehensive research on developing, validating, and evaluating teaching materials that effectively integrate ethnomathematics content. The study aimed to create teaching materials within the context of ethnomathematics to evaluate students' mathematical creative thinking. This endeavor followed the ADDIE research and development model, encompassing analysis, development, design, implementation, and evaluation. Small-group testing was undertaken involving 10 participants, while field testing involved 35 respondents. The validation process involved both media, and material experts to ensure the suitability of the teaching materials for development. The findings indicated that the teaching materials received validation from experts, confirming their quality and appropriateness. Additionally, student feedback showed that the materials were not only valid but also engaging and intellectually stimulating, meeting the criteria for an effective educational resource. In summary, the development of teaching materials stands out as a valuable asset in evaluating students' mathematical creative thinking abilities. This research contributes to the field of mathematics education, especially in mathematics teaching and learning